2000
DOI: 10.1023/a:1019022230731
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The 1997 hospital financing reform has been supposed to reduce considerable inefficiencies in the provision of hospital care in Austria. This paper focuses on the changes in hospital productivity between 1994 and 1998, thus including three years before the reform and two years after the reform. Using Data Envelopment Analysis we calculated the input-based Malmquist index, which is then decomposed into indices of pure technical efficiency change, scale efficiency change and technology change. The results illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 8 publications
0
15
1
2
Order By: Relevance
“…Sommersguter [109] explored productivity changes in Austrian hospitals after and before hospital financing reform. The results illustrated a considerably positive shift in technology between 1996 and 1998, whereas the intended enhancement in technical efficiency had not yet occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sommersguter [109] explored productivity changes in Austrian hospitals after and before hospital financing reform. The results illustrated a considerably positive shift in technology between 1996 and 1998, whereas the intended enhancement in technical efficiency had not yet occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the majority of hospitals could increase their efficiency and reduce their costs by diversification of the offered output mix. One study [109] used a sample of government and non-government hospitals to explore productivity changes after and before hospital financing reform. Four studies [5, 95, 106, 107] analysed hospital productivity of a sample of general acute-care hospitals, including teaching hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the practice of charging maximum tariffs. Systematically extending the limits of Diagnosis-Related Group (DRG) coding was the reason for the ‘artificial’ technological progress in the Austrian hospital sector, which was identified immediately after the introduction of the DRG financing [85]. A recent study in Germany found evidence of selective up-coding regarding the birth weight of newborns, which is a major remuneration element in the German DRG-based hospital reimbursement system [86].…”
Section: Proposal To Link Different Typologies Of Corruptionmentioning
confidence: 99%
“…Estes índices parciais são importantes porque permitem verifi car se um eventual aumento da efi ciência relativa de um período para o outro deve ser atribuído ao aumento da produtividade da unidade avaliada ou à contração da fronteira de produção. 8,17 Uma das principais vantagens da aplicação de DEA para identifi cação da fronteira de efi ciência está no fato de que as medidas de mudanças de produtividade podem ser analisadas a partir de dois componentes distintos: as "mudanças na tecnologia" (decorrente do deslocamento da fronteira no tempo) e as "mudanças na efi ciência técnica" (desempenho comparativo da unidade analisada). Nos referidos estudos, houve acompanhamento dos resultados por, no míni-mo, quatro anos consecutivos e, em ambos os casos, observou-se melhora expressiva da fronteira tecnoló-gica nos anos que sucederam a reforma, sem alteração signifi cativa na efi ciência técnica dos hospitais.…”
Section: O íNdice De Malmquist Orientado a Input é Dado Porunclassified